The impact of wages on the labour market in the Republic of Croatia - Prvonožec, Stela (Oeconomica Jadertina, 2020)
Labour market, value of wages and standard of living are inextricably linked determinants of economic development. Croatian GDP, living standards and purchasing power of the population are among the lowest in Europe. Wage growth in Croatia is present, but, as in most Central and Eastern European countries, it is not accompanied by an increase in labour productivity. The majority of the income of the Croatian population is spent on food, which is associated with low productivity of the economy. There is a significant dependence on social transfers in the structure of the household income, which, for a significant share of the population, represent the difference between poverty and relatively normal life. Croatia has failed to create economic models that enable economic growth through technological progress and strengthening of labour productivity. In order to improve the standard of living in the Republic of Croatia, it is necessary to solve the structural problems present in the labour market and create economic policies that encourage economic growth. This paper analyses the relationship between the value of wages, labour market and standard of living in the Republic of Croatia. The hypothesis is that structural problems in the Croatian labour market affect the value of wages, and consequently the standard of living of Croatian citizens. The aim of this paper is to analyse the structural problems on the labour market in Croatia and their impact on the value of wages. The purpose of this paper is to point out the importance of an efficient labour market in the national economy of the Republic of Croatia.